Distraction in Australian language education policy: a call to re-centre language rights - Steele, Carly; Oliver, Rhonda (Taylor & Francis, 2024)
In this paper, we provide an overview of the policies that have existed in relation to Australian First Nations students’ languages, and English language and literacy learning before exploring how the politics of distraction manifests in this context. We then share our findings of an analysis of Australian language education policies for First Nations children and the media discourses which surround them. We argue that, in the context of First Nations languages and language learners, ‘language’ is conflated with either ‘literacy’ or ‘culture’ to distract from the sovereign language rights of First Nations peoples in Australia. We draw on the notion of ‘policy narrowing’ to explain this policy distraction and the ways in which it reproduces educational inequities for First Nations students in the Australian schooling system. To counter this, and the surrounding media discourses, governing educational bodies should re-centre language rights and language learner diversity in policymaking.